2018
DOI: 10.3389/fnmol.2018.00295
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid 1 Receptor Signaling on Hippocampal GABAergic Neurons Influences Microglial Activity

Abstract: Microglia, the resident immune cells of the brain, play important roles in defending the brain against pathogens and supporting neuronal circuit plasticity. Chronic or excessive pro-inflammatory responses of microglia damage neurons, therefore their activity is tightly regulated. Pharmacological and genetic studies revealed that cannabinoid type 1 (CB1) receptor activity influences microglial activity, although microglial CB1 receptor expression is very low and activity-dependent. The CB1 receptor is mainly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 68 publications
1
28
0
Order By: Relevance
“…For quantitative analysis, two‐photon Z ‐stacks were automatically reconstructed using a self‐customized python‐based script (Ativie et al , ). Reconstructions were visually checked using the ImageJ plugin “simple neurite tracer” (Appendix Fig S6).…”
Section: Methodsmentioning
confidence: 99%
“…For quantitative analysis, two‐photon Z ‐stacks were automatically reconstructed using a self‐customized python‐based script (Ativie et al , ). Reconstructions were visually checked using the ImageJ plugin “simple neurite tracer” (Appendix Fig S6).…”
Section: Methodsmentioning
confidence: 99%
“…Neuronal loss during neurodegeneration and consequent loss of these interacting surface proteins activates microglia, thus CX3CR1 is believed to be neuroprotective in neurodegenerative diseases [151]. We are not aware of any studies that directly investigated CB2R-mediated neuron-microglia interaction, but we have previously shown that CB1Rs on GABAergic neurons play a role in neuron-microglia communication via fractalkine/CX3CR1 [153]. Moreover, AEA, and possibly 2-AG as well, can be secreted via microglial extracellular membrane vesicles and by activating CB1R inhibit synaptic transmission of GABAergic neurons [154] (Figure 2).…”
Section: Cb2rs In Neuron-microglia Interactionmentioning
confidence: 99%
“…Endocannabinoid signaling may also be beneficial because of its impact on attenuating neurotoxicity and neuroinflammation. It has been shown that deletion of CB1 accelerates brain aging through tumor necrosis factor α (TNF-α) [166], while CB1 agonism decreases neuroinflammation [167]. There have also been studies on FAAH inhibition impact on decreasing neuroinflammation [168] and exitoxicity in rodent models [169].…”
Section: Neurodegenerationmentioning
confidence: 99%